Experience in designing protective workwear for patients with thermal injury - Shaizadanova, Gulnar; Kucharbaeva, Kaldigul; Mokeeva, Natalia; Yeraliyeva, Mira; Toremuratova, Galiya (International Journal of Innovative Research and Scientific Studies, 2025)
The use of information technology is an integral step in the creation of automation systems in medical institutions for the selection of special-purpose clothing in an automated mode. In this work, a computer program "MedicalApp" was developed using analysis, systematization, and research of medical procedures carried out in the treatment of burns and topographic zones of their conduct. The purpose of this work is to base it on the database containing the classification of the degree and depth of thermal damage to the human body, the developed topography of medical procedures, taking into account the schemes of dynamic poses of patients with thermal lesions, and developed sets of special-purpose clothing for patients with thermal lesions, to automatically calculate the area of thermal damage to the surface of the human body, determine the degree and depth of the burn, taking into account the severity of the thermal lesion, and ensure the selection of the developed sets of special-purpose clothing for patients with thermal lesions. Special-purpose clothing sets are designed taking into account the requirements of functionality, specific features of medical procedures, and provide comfort and freedom of movement to the patient, as well as convenience to medical personnel during medical procedures. In solving this problem, studies of antibacterial tissue, systematization and distribution of therapeutic procedures by topographic zones, and development of schemes of dynamic poses of patients with thermal lesions were used.